2020
DOI: 10.1101/2020.02.01.929976
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potent neutralization of 2019 novel coronavirus by recombinant ACE2-Ig

Abstract: 2019-nCoV, which is a novel coronavirus emerged in Wuhan, China, at the end of 2019, has caused at least infected 11,844 as of Feb 1, 2020. However, there is no specific antiviral treatment or vaccine currently. Very recently report had suggested that novel CoV would use the same cell entry receptor, ACE2, as the SARS-CoV. In this report, we generated a novel recombinant protein by connecting the extracellular domain of human ACE2 to the Fc region of the human immunoglobulin IgG1. An ACE2 mutant with low catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
92
2
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 26 publications
0
92
2
3
Order By: Relevance
“…Although there are four amino acid variations of S protein between 2019-nCoV and SARS-CoV, 2019-nCoV can also bind to the human angiotensinconverting enzyme 2 (ACE2), the same host receptor for SARS-CoV, as 2019-nCoV can bind to the ACE2 receptor from the cells from human, bat, civet cat, and pig, but it cannot bind to the cells without ACE2 11,[33][34][35] . A recombinant ACE2-Ig antibody, a SARS-CoV-specific human monoclonal antibody, and the serum from a convalescent SARS-CoV-infected patient, which can neutralize 2019-nCoV, confirmed ACE2 as the host receptor for 2019-nCoV [36][37][38][39] . The high affinity between ACE2 and 2019-nCoV S protein also suggested that the population with higher expression of ACE2 might be more susceptible to 2019-nCoV 40,41 .…”
Section: Characteristics Of 2019 Novel Coronavirusmentioning
confidence: 89%
“…Although there are four amino acid variations of S protein between 2019-nCoV and SARS-CoV, 2019-nCoV can also bind to the human angiotensinconverting enzyme 2 (ACE2), the same host receptor for SARS-CoV, as 2019-nCoV can bind to the ACE2 receptor from the cells from human, bat, civet cat, and pig, but it cannot bind to the cells without ACE2 11,[33][34][35] . A recombinant ACE2-Ig antibody, a SARS-CoV-specific human monoclonal antibody, and the serum from a convalescent SARS-CoV-infected patient, which can neutralize 2019-nCoV, confirmed ACE2 as the host receptor for 2019-nCoV [36][37][38][39] . The high affinity between ACE2 and 2019-nCoV S protein also suggested that the population with higher expression of ACE2 might be more susceptible to 2019-nCoV 40,41 .…”
Section: Characteristics Of 2019 Novel Coronavirusmentioning
confidence: 89%
“…Synthetic antibodies represent an exciting, novel therapeutic avenue. One strategy being explored is to fuse ACE2 to Fc IgG, with the hypothesis that this synthetic antibody would serve as a decoy receptor, preventing cellular binding of the virion (143).…”
Section: Neutralizing Antibodies and Decoy Proteinsmentioning
confidence: 99%
“…The genome sequence of SARS-CoV-2 is 82% identical to SARS-CoV [4]. Angiotensin converting enzyme II (ACE2) was identified as the cell entry receptor of SARS-CoV-2 to infect human, similar to SARS-CoV [6]. ACE2 belongs to the angiotensin-converting enzyme family and catalyzes the cleavage of angiotensin II into the vasodilator angiotensin 1-7.…”
Section: Introductionmentioning
confidence: 99%